Retrofit of grass swales with outflow controls for enhancing drainage capacity - Mantilla, Ivan; Flanagan, Kelsey; Broekhuizen, Ico; Muthanna, Tone Merete; Marsalek, Jiri; Viklander, Maria (Journal of Hydrology, 2024)
Reduction of runoff flow peaks and volumes is one of the performance objectives of grass swales in the context of Green Stormwater Infrastructure (GSI). Towards this end, a study of the feasibility of using a retrofitted swale outlet control weir (SOCW) to reduce runoff volume and peak flow, by enhancing swale runoff storage and infiltration into swale soils, was conducted in Luleå, Northern Sweden. Experimental field work consisted of 43 irrigation-driven runoff experiments, mimicking rainfall events with return periods between 1- to 50-years, with a constant intensity and duration of 30 min, in a 30-m long grass swale section. Experimental results confirmed that, under the tested conditions, swales with the retrofitted outflow control, reduced runoff volumes and peak flows. Such reductions ranged from 32 percentage points (for 2-year) to 1 and 4 percentage points (for 50-year return period) for runoff volumes and peak flows, respectively. Outcomes of scenarios with outflow controls clearly indicated a decreasing performance with increasing flow rates (and irrigation event return periods). Furthermore, the retrofitted swale controlled the outflow release during less frequent 20 to 50-year events, which would contribute to reducing flood risks in downstream urban areas. Validerad;2024;Nivå 2;2024-07-22 (signyg); Fulltext licence: CC BY